The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/ajpy.12062
|View full text |Cite
|
Sign up to set email alerts
|

Can we fight stigma with science? The effect of aetiological framing on attitudes towards anorexia nervosa and the impact on volitional stigma

Abstract: The present study experimentally investigated the way in which exposure to various aetiological explanations of anorexia nervosa (AN) differentially affected stigmatisation and behavioural intention outcomes. University students (N = 161) were randomly assigned to read one of four aetiological vignettes presenting the causes of AN as biological/genetic, socio-cultural, environmental, or multifactorial. Results indicate that those who received a socio-cultural explanation made stronger socio-cultural causal att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(62 citation statements)
references
References 23 publications
(58 reference statements)
3
58
1
Order By: Relevance
“…An average score for each subscale was created for analysis. Previous research (e.g., Bannatyne & Abel, 2014) has reported good internal consistencies ranging from .82 (sociocultural) to .84 (biogenetic). Reliability analyses for the current study revealed similar internal consistencies (.86 and .83, respectively).…”
Section: Downloaded By [Northeastern University] At 15:04 02 Februarymentioning
confidence: 89%
See 4 more Smart Citations
“…An average score for each subscale was created for analysis. Previous research (e.g., Bannatyne & Abel, 2014) has reported good internal consistencies ranging from .82 (sociocultural) to .84 (biogenetic). Reliability analyses for the current study revealed similar internal consistencies (.86 and .83, respectively).…”
Section: Downloaded By [Northeastern University] At 15:04 02 Februarymentioning
confidence: 89%
“…Participants were asked to indicate on a 7-point Likert scale, ranging from 1 (does not contribute at all) to 7 (main contributing factor) the extent to which nine different factors contribute to the development of AN. In line with previous research (e.g., Bannatyne & Abel, 2014), the Causal Attributions Scale (Crisafulli et al, 2008) was separated into two subscales for analysis: biogenetic attributions and sociocultural attributions. An average score for each subscale was created for analysis.…”
Section: Downloaded By [Northeastern University] At 15:04 02 Februarymentioning
confidence: 93%
See 3 more Smart Citations